Difference between revisions of "2013 Mock AIME I Problems/Problem 11"
(created solution page) |
(→Solution) |
||
Line 3: | Line 3: | ||
== Solution == | == Solution == | ||
− | <math>\ | + | |
+ | For some integer <math>n</math>, let <math>s_n</math> be <math>a^n+b^n+c^n</math>. | ||
+ | |||
+ | Note that <math>(X+1)(Y+1) = XY+X+Y+1</math>, so, to answer the problem, it suffices to know <math>XY</math> and <math>X+Y</math>. | ||
+ | |||
+ | Let <math>f(x)=x^3+2x-1=0</math>. First, note the arbitrary decision in the expression <math>\tfrac a b + \tfrac b c + \tfrac c a</math>. Why must <math>a</math> be over <math>b</math>, but not <math>b</math> over <math>a</math>? From this observation, we can deduce that the aforementioned two possible values of this sum are <math>\tfrac a b + \tfrac b c + \tfrac c a</math> ([[WLOG]] let this be <math>X</math>) and <math>\tfrac b a + \tfrac c b + \tfrac a c</math> (WLOG let this be <math>Y</math>). From these definitions and the knowledge from [[Vieta's Formulas]] that <math>abc=1</math>, we can now combine fractions to get the following: | ||
+ | \begin{align*} | ||
+ | X = \frac a b + \frac b c + \frac c a &= \frac{a^2c+ab^2+bc^2}{abc} = a^2c+ab^2+bc^2 \\ | ||
+ | Y = \frac b a + \frac c b + \frac a c &= \frac{b^2c+ac^2+a^2b}{abc} = b^2c+ac^2+a^2b | ||
+ | \end{align*} | ||
+ | Notice that these terms appear in the expansion of <math>(a+b+c)^3</math>, so we look for a way to get a value for <math>a+b+c</math>. Fortunately, we can use Vieta again to see that <math>a+b+c=0</math>. Thus, <math>(a+b)^3=0</math>, and so <math>a^3+b^3+c^3+3(a^2b+a^2c+ab^2+b^2c+ac^2+bc^2)+6abc=0</math>, or, by substitution and recalling that <math>abc=1</math>, <math>s_3+3(X+Y)+6=0</math>. To get <math>s_3</math>, we think [[Newton Sums]], which give us the following: | ||
+ | \begin{align*} | ||
+ | s_3 + 0s_2 + 2s_1 + 3(-1) &= 0 \\ | ||
+ | s_3 &= -2(a+b+c)+3 \\ | ||
+ | s_3 &= 3 | ||
+ | \end{align*} | ||
+ | Thus, the equation <math>s_3+3(X+Y)+6=0</math> becomes <math>3+3(X+Y)+6=0</math>, so <math>X+Y=-3</math>. | ||
+ | |||
+ | Now that we have <math>X+Y</math>, we desire to find <math>XY</math>. Note that Vieta gives us <math>ab+bc+ac=2</math>, so, because <math>abc=1</math>, by substitution <math>\tfrac1 c + \tfrac1 a +\tfrac1 b = s_{-1} = 2</math>. By substituting our values for <math>X</math> and <math>Y</math> into <math>XY</math>, we see the following: | ||
+ | \begin{align*} | ||
+ | XY &= (\frac a b + \frac b c + \frac c a)(\frac b a + \frac c b + \frac a c) \\ | ||
+ | &= 1 + \frac{ac}{b^2} + \frac{a^2}{bc} + \frac{b^2}{ac} + 1 + \frac{ab}{c^2} + \frac{bc}{a^2} + \frac{c^2}{ab} + 1 \\ | ||
+ | \text{Recalling that } abc=1 &\text{, we have the following by substitution:} \\ | ||
+ | XY &= 3 + a^3+b^3+c^3 + \frac1{a^3} + \frac1{b^3} + \frac1{c^3} \\ | ||
+ | &= 3+s_3+s_{-3} | ||
+ | \end{align*} | ||
+ | Now, we desire to find <math>s_{-3}</math>. To do this, we try to think of a function <math>g(x)</math> whose roots are <math>\tfrac1a, \tfrac1b,</math> and <math>\tfrac1c</math>. <math>g(x)=-x^3f(\tfrac1x)=x^3-2x^2-1</math> will work. Using Newton Sums again and recalling that <math>s_{-1}=2</math>, we see that: | ||
+ | \begin{align*} | ||
+ | s_{-2}+(-2)s_{-1}+2(0) &= 0 \\ | ||
+ | s_{-2} &= 4 | ||
+ | \end{align*} | ||
+ | We use Newton Sums a third time: | ||
+ | \begin{align*} | ||
+ | s_{-3}+(-2)s_{-2}+0s_{-1}+3(-1) &= 0 \\ | ||
+ | s_{-3} &= 8 + 3 = 11 | ||
+ | \end{align*} | ||
+ | Thus, because <math>s_{-3}=11</math> and <math>s_3=3</math>, we have that <math>XY=3+s_3+s_{-3}=3+3+11=17</math>. | ||
+ | |||
+ | Thus, we can now find our desired answer: | ||
+ | \begin{align*} | ||
+ | (X+1)(Y+1) &= XY + (X+Y) + 1 \\ | ||
+ | &= 17 - 3 + 1 \\ | ||
+ | &= \boxed{015}. | ||
+ | \end{align*} | ||
== See also == | == See also == |
Revision as of 15:31, 30 July 2024
Problem
Let and be the roots of the equation , and let and be the two possible values of Find .
Solution
For some integer , let be .
Note that , so, to answer the problem, it suffices to know and .
Let . First, note the arbitrary decision in the expression . Why must be over , but not over ? From this observation, we can deduce that the aforementioned two possible values of this sum are (WLOG let this be ) and (WLOG let this be ). From these definitions and the knowledge from Vieta's Formulas that , we can now combine fractions to get the following: \begin{align*} X = \frac a b + \frac b c + \frac c a &= \frac{a^2c+ab^2+bc^2}{abc} = a^2c+ab^2+bc^2 \\ Y = \frac b a + \frac c b + \frac a c &= \frac{b^2c+ac^2+a^2b}{abc} = b^2c+ac^2+a^2b \end{align*} Notice that these terms appear in the expansion of , so we look for a way to get a value for . Fortunately, we can use Vieta again to see that . Thus, , and so , or, by substitution and recalling that , . To get , we think Newton Sums, which give us the following: \begin{align*} s_3 + 0s_2 + 2s_1 + 3(-1) &= 0 \\ s_3 &= -2(a+b+c)+3 \\ s_3 &= 3 \end{align*} Thus, the equation becomes , so .
Now that we have , we desire to find . Note that Vieta gives us , so, because , by substitution . By substituting our values for and into , we see the following: \begin{align*} XY &= (\frac a b + \frac b c + \frac c a)(\frac b a + \frac c b + \frac a c) \\ &= 1 + \frac{ac}{b^2} + \frac{a^2}{bc} + \frac{b^2}{ac} + 1 + \frac{ab}{c^2} + \frac{bc}{a^2} + \frac{c^2}{ab} + 1 \\ \text{Recalling that } abc=1 &\text{, we have the following by substitution:} \\ XY &= 3 + a^3+b^3+c^3 + \frac1{a^3} + \frac1{b^3} + \frac1{c^3} \\ &= 3+s_3+s_{-3} \end{align*} Now, we desire to find . To do this, we try to think of a function whose roots are and . will work. Using Newton Sums again and recalling that , we see that: \begin{align*} s_{-2}+(-2)s_{-1}+2(0) &= 0 \\ s_{-2} &= 4 \end{align*} We use Newton Sums a third time: \begin{align*} s_{-3}+(-2)s_{-2}+0s_{-1}+3(-1) &= 0 \\ s_{-3} &= 8 + 3 = 11 \end{align*} Thus, because and , we have that .
Thus, we can now find our desired answer: \begin{align*} (X+1)(Y+1) &= XY + (X+Y) + 1 \\ &= 17 - 3 + 1 \\ &= \boxed{015}. \end{align*}